2018
DOI: 10.1259/bjr.20180437
|View full text |Cite
|
Sign up to set email alerts
|

Computer-based automatic classification of trabecular bone pattern can assist radiographic bone quality assessment at dental implant site

Abstract: Computer-aided trabecular bone pattern assessment based on morphometric parameters could assist objectivity in clinical bone quality classification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 37 publications
0
11
0
3
Order By: Relevance
“…In the current study, morphometric bone parameters from a high‐resolution CBCT were used to account for the full 3D trabecular structure. Previous studies have shown that trabecular bone morphometric parameters can be used in cluster analysis to automatically distinguish bone types (Nicolielo et al, ). Based on these parameters, an automatic classifier distinguished between three types of 3D trabecular pattern, namely sparse, intermediate, and dense.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current study, morphometric bone parameters from a high‐resolution CBCT were used to account for the full 3D trabecular structure. Previous studies have shown that trabecular bone morphometric parameters can be used in cluster analysis to automatically distinguish bone types (Nicolielo et al, ). Based on these parameters, an automatic classifier distinguished between three types of 3D trabecular pattern, namely sparse, intermediate, and dense.…”
Section: Discussionmentioning
confidence: 99%
“…The morphometric bone parameter selection was based on our previous work (Nicolielo et al, ) in which linear discriminant analysis was used to find the best combination of morphometric parameters separating trabecular bone in three bone types: (i) sparse—related to a loose bone structure, (ii) intermediate—related to a well‐structured trabecular bone, and (iii) dense bone types—related to a massive bone area with little space between the trabeculae (Figure ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All these variables have a significant impact on the conditions and goals of the procedure and should be recognized and taken into account at the planning stage [ 10 , 15 , 20 , 21 , 22 , 29 , 30 , 32 , 46 ]. Current literature describes bony conditions for immediate implants [ 20 , 31 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 47 ]. Some of them focus primarily on internal bone structure and bone density [ 36 , 39 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The post-extraction socket orifice is the only entry, and therefore, the study of the most commonly encountered patterns of bone anatomy in this maxillary region is desirable. In the available literature, there are a few publications on the shape and quality of bone of the alveolar process, and there is a great need to describe the alveolar bone typical anatomy directly after tooth extraction in terms of the possibility of immediate implantation [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. In an animal model, immediately after a tooth extraction, the molecular and histologic study by Marconcini et al reported that myofibroblasts were up-regulated in the first 15-days of the healing period; thus, the excessive tension of these cells during the epithelial closure of the socket may be managed by the use of collagen, an immediate implant placement, or a provisional prosthesis [ 45 ].…”
Section: Introductionmentioning
confidence: 99%